The Effectiveness of Enforcement of Whipping Punishment to Provide a Deterrent Effect in the Enforcement of Islamic Shariat in Banda Aceh City - Dm Maulidia Rahmi; Tjahyo Suprayogo; Rusmiyati, Rusmiyati (INFOKUM, 2025)
Aceh Province is one of the provinces in Indonesia that is based on the implementation of Islamic law and has its own regional regulations called qanun. One of the qanuns in Aceh Province is Aceh Qanun Number 6 of 2014 concerning Jinayat Law. The desired goal of implementing the caning punishment is to reduce cases of violations of Islamic law in Aceh, but in reality violations of Islamic law still continue to occur. Therefore, it is considered important to conduct research related to the effectiveness of the caning punishment in order to provide a deterrent effect in enforcing Islamic law in Banda Aceh City. This study was conducted to analyze the effectiveness of the enforcement of the caning punishment by the Banda Aceh City government in order to provide a deterrent effect in enforcing Islamic law in Banda Aceh City, using Ryass Rasyid's theory on the main tasks of government, and using qualitative research methods with exploratory methods. Data collection techniques through purposive sampling. Data were collected through observation, interviews, and documentation studies. The results of the discussion in this study are that the enforcement of the caning punishment has not been effective in providing a deterrent effect as seen from 3 (three) aspects, namely security, order, and justice. Inhibiting factors for enforcing caning punishment are 1) Lack of human resources; 2) Lack of budget. The supporting factors are the community who participate in monitoring and reporting to the authorities if there are violations. Efforts made by the government in enforcing caning punishment in order to provide a deterrent effect can be seen from: 1) Cooperating between institutions; 2) Conducting socialization to the community; 3) Consistent with the rules that have been made. The author's suggestions or input to various stakeholders related to the implementation of the qanun jinayat in enforcing Islamic law in Banda Aceh City are as follows: 1) Adding human resources according to agency needs; 2) Increasing the budget; 3) Conducting socialization to the community regarding the understanding of the rules in force in Banda Aceh City.